Structural Design and Kinematics Analysis of a Human Lower Limb Rehabilitation Device - Zhang Enhui; Zhao Changrong; Ren Shichao (Jixie chuandong)
A human lower limb rehabilitation device based on a planar five-bar mechanism was introduced, aiming at meeting the early, mid and late rehabilitation training needs of stroke patients who are bedridden after surgery. This device has the characteristics of simplicity and reliability, and can be placed at the end of the bed or moved with the patient's walking. The device mainly consists of a lower mobile platform, a manual lifting component, an upper power transmission mechanism, and left and right training mechanisms. Sensors were attached to the universal joint brackets of the ankle and knee joints, allowing real-time collection and feedback of the patient motion information. Through kinematics analysis and Adams software simulation, the results show that adjusting the initial phase of the double crank of the device can change the motion track of the joint points, thus obtaining the range of motion of human lower limb joints under different motion modes, achieving the purpose of horizontal training and walking training, and meeting the training needs of patients in different rehabilitation stages.